Potential application of dry medicinal plant powders in controlling black spot on Chinese kale and chili anthracnose diseases - Dethoup, Tida; Jantasorn, Arom (Agriculture and Natural Resources, 2023)
Importance of the work: Chinese kale and chili are important vegetables in Thailand; however, their production is affected by diseases. Objective: To evaluate the efficacy of plant powders against black spot disease on Chinese kale and chili anthracnose disease through greenhouse tests and field trials. Materials and Methods: The efficacy was evaluated of 20 plant powders in inhibiting Alternaria brassicicola (cause of black spot disease) and Colletotrichum truncatum (cause of anthracnose disease) at 50 g/L and 25 g/L in vitro along with testing the protective and curative activities of the selected plant powders against black spot disease on Chinese kale and chili anthracnose disease under greenhouse and field conditions. Results: The results from the greenhouse conditions showed that the Syzygium aromaticum (clove) and Zingiber cassumunar (phlai) powders had significant fungicidal activity in controlling black spot disease on Chinese kale with disease reduction ranges of 38.64–41.95% and 29.87–33.95% in the protective and curative tests, respectively. In addition, both plant powders demonstrated high levels of activity in controlling black spot on Chinese kale (36.3% and 32.76%, respectively), whereas the Coscinium fenestratum and Curcuma longa powders reduced the incidence of this disease by 29.43% and 26.83%, respectively, compared to the negative results from the controls (with water) in the field trials. The S. aromaticum and Z. cassumunar plant powders both showed strong activity in controlling anthracnose disease in leaves and detached fruit. Main finding: Syzygium aromaticum and Zingiber cassumunar powders showed potent fungicidal activity in controlling Chinese kale and chili diseases.